Rekonstruksi Hukum Pasar Modal Syariah dalam Memberi Jaminan Kepastian Hukum - Subaidi Subaidi (Program Pascasarjana Universitas Ibrahimy, 2017)
The shari'a concept in Islamic capital market industry is generally considered haven’t been able to provide guaranteeing legal certainty. Public that has been accustomed to using conventional concept feel more secure with guaranteeing legal certainty of conventional concept in capital market industry. That public confidenceissue became a positive correction in developing Islamic capital market industry in Indonesia. Guaranteeing legal certainty is indispensable in the legal system of society, so that required a legal reconstruction in Islamic capital market industry in Indonesia. The questions are; what is the importance of law in Islamic capital market industry and how is the configuration of law reconstruction in Islamic capital market industry in the future.